Model Struktural Hubungan Dimensi Consumer-Based Brand Equity dan Keputusan Pembelian Pizza Hut - Mutmainah, Isbandriyati; Yulia, Iis Anisa; Gunawan, Amelia (Research Center and Case Clearing House PPM School of Management, 2024)
A competitive business environment makes brands as an important asset for companies to compete, so they must A competitive business environment makes brands an important asset for companies to compete, so they must build brand equity to increase their differentiation capabilities. Brand equity is important in increasing company performance through its positive influence on purchasing decisions. Using the SEM analysis method, this study identified a structural relationship between the dimensions of brand equity and the impact of brand equity on purchasing decisions, a case of Pizza Hut consumers. In this study, brand equity uses the CBBE dimensions: brand awareness, brand associations, perceived quality, and brand loyalty. The survey was conducted on 329 Pizza Hut consumers living in Jabodetabek. The findings from this study indicate that brand awareness and brand associations affect perceived quality, while perceived quality and brand associations affect brand loyalty. Brand awareness, perceived quality, and brand loyalty directly affect purchasing decisions, while the direct impact of brand association is not significant. Brand awareness indirectly affects purchasing decisions through the mediation of brand loyalty, and brand associations indirectly affect purchasing decisions through the mediation of perceived quality and brand loyalty. These results recommend the importance of strategies to build brand equity, especially in building loyalty amid the increasing prevalence of similar fast food